PF-19 Professional Wellness for Veterinarians - Nienke Endenburg (Hemera Zoa, 2018)
Personal and professional wellness of veterinarians and veterinary staff are receiving increased attention in veterinary publications and conferences, social media and the non-veterinary press. Recent suicides of high-profile, socially-harassed or victimized veterinarians have caused consternation within the profession. There is an increased recognition that stress and compassion fatigue coupled with a demanding workplace environment are adversely affecting the mental well-being and physical health of veterinarians.